Comparison of coronary heart disease genetic assessment with conventional cardiovascular risk assessment in primary care: reflections on a feasibility study - Qureshi, Nadeem; Kai, Joe; Middlemass, Jo; Dhiman, Paula; Cross-Bardell, Laura; Acharya, Jayshree; Li, Ka Wan; Humphries, Steve E.; Standen, Penny (Cambridge University Press, 2015)
This study assesses the feasibility of collecting genetic samples and self-reported outcome measures after cardiovascular risk assessment, and presenting the genetic test results to participants. Coronary heart disease (CHD) genetic tests are increasingly available through direct-to-consumer marketing, but their potential clinical impact on cardiovascular risk assessment is unclear. Observational study in 10 British general practices in Central England. A total of 320 individuals, who had completed conventional cardiovascular risk assessment, were offered CHD genetic test, with follow-up outcome questionnaire at eight months for lifestyle change and State-Trait Anxiety. A total of 119 (37%) participants returned genetic test specimens, with over a third reporting family history of CHD in a specified relative; 79 (66.4%) were categorized above-average risk on conventional cardiovascular risk assessment, 65 of whom (82.3%) were only average risk on genetic assessment. The dietary fat questionnaire was poorly completed while study participation was not associated with increased anxiety (mean increase in anxiety score=2.1; 95% CI −0.1–4.3; P=0.06). As a feasibility study, over a third of individuals offered genetic testing in primary care, as part of CVD risk assessment, took up the offer. Although intervention did not appear to increase anxiety, this needs further evaluation. To improve generalizability and effect size, future studies should actively engage individuals from wider socio-economic backgrounds who may not have already contemplated lifestyle change. The current research suggests general practitioners will face the clinical challenge of patients presenting with direct-to-consumer genetic results that are inconsistent with conventional cardiovascular risk assessment.